Pengaruh Perputaran Piutang dan Perputaran Persediaan terhadap Profitabilitas (ROA) Pada Perusahaan Rumah Sakit yang terdaftar di BEI Periode 2020-2024 - Mutiara Hayandani; Anggun Fitria Novianti; Fadila Siti Nuraeni; Djalalludin Akbar; Alfiana Alfiana (INDO PUBLISHING, 2026)
This study aims to explore the impact of receivables rotation and inventory rotation on Return on Assets (ROA). The focus of this study is hospital companies listed on the Indonesia Stock Exchange (IDX). The population in this study includes all hospitals listed on the IDX from 2020 to 2024. The sampling methodology applied was purposive sampling, thus selecting a number of companies that met the research requirements. The research approach used a quantitative method with panel data regression analysis. The data used were secondary data taken from the company's annual financial reports. The regression model selection was carried out through the Chow test, the Hausman test, and the Lagrange Multiplier test, which indicated that the Random Effects Model (REM) was the most appropriate model. The findings of this study indicate that partially, receivables rotation has no significant impact on ROA, while inventory rotation has a positive and significant effect on ROA. Simultaneously, receivables rotation and inventory rotation have a significant effect on ROA. This research is expected to be useful for company management as a consideration in managing receivables and inventory to increase the company's profitability, as well as serve as a reference for further research in the financial field.